FINANCIAL LITERACY AS THE KEY TO THE FINANCIAL BEHAVIOR OF RETIRED CIVIL SERVANT: A STUDY OF LOCUS OF CONTROL MEDIATION - Dudya Dermawan (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2025)
This study aims to analyze the influence of Islamic financial literacy and financial self-efficacy on the financial management behavior of retired Civil Servants (ASN) in the Jabodetabek area, and to examine the mediating role of locus of control in this relationship. Employing an explanatory quantitative approach, the research involved 100 purposively selected retired ASN respondents. Primary data was collected using structured questionnaires and analyzed via the Structural Equation Modeling (SEM) method. The results indicate that Islamic financial literacy, financial self-efficacy, and locus of control partially have a positive and significant influence on financial management behavior. A crucial finding of this study confirms that locus of control plays a dominant and key mediating role in translating the influence of financial literacy and financial self-confidence into the retired servants' financial management behavior. These findings bear important implications for relevant institutions in designing retirement education programs that focus not only on Sharia knowledge but also on the psychological reinforcement of financial self-control.